A Contextual Approach in Islamic Religious Education Learning - Muhammad Syukri; Endang Sulhiawati (Indonesian Journal of Education and Science, 2026)
Islamic Religious Education (IRE) plays a strategic role in fostering learners’ cognitive, affective, and psychomotor development through the integration of religious knowledge, values, and real-life practice. However, IRE learning is often characterized by abstract and text-oriented instruction, which limits students’ meaningful engagement. This study aims to examine the implementation of the Contextual Teaching and Learning (CTL) approach in Islamic Religious Education, identify facilitating and inhibiting factors affecting its application, and analyze its contribution to meaningful learning outcomes. Employing a qualitative literature review design, this study analyzed relevant books and peer-reviewed journal articles published within the last ten years. Data were collected through systematic documentation and analyzed using thematic content analysis to identify recurring concepts, strategies, and outcomes related to CTL in IRE contexts. The findings indicate that CTL in Islamic Religious Education is conceptually grounded in constructivist learning theory, cognitive psychology, and the philosophical foundations of Islamic education. CTL implementation is characterized by experiential learning strategies, including problem-based learning, collaborative activities, reflection, and the use of learners’ real-life environments as instructional resources. Teacher pedagogical competence, curriculum flexibility, institutional support, and learning resources emerged as key facilitating factors, while limited infrastructure, insufficient training, time constraints, and technological challenges were identified as major barriers. Furthermore, the contextual approach contributes significantly to meaningful learning outcomes across cognitive, affective, and psychomotor domains by enhancing understanding, motivation, value internalization, and behavioral practice. This study concludes that CTL serves as a pedagogically relevant approach for strengthening meaningful and holistic learning in Islamic Religious Education.